R&D: Cornerstone of the Knowledge Economy - Richert, Evan (Maine Policy Review, 2014)
Maine has made progress toward achieving the goals set out 13 years ago in the State Planning Office’s publication “30 and 1000.” That publication projected that if 30 percent of the state’s adults had at least four-year degrees and if businesses, academia, and government were spending $1,000 per employed worker on research and development, Maine’s per capita income would reach the national average. The state still has a ways to go. Today it is estimated that the R&D threshold is about $1,600 per employed worker. Business will need to nearly double its effort to reach its share of the goal. That will require continued retooling of traditional industry and emergence of new, high performing R&D businesses. An annual commitment by state government of 5 to 7 percent of the total requirement would help businesses, universities, and research institutions leverage the rest.
Keywords: Maine; research and development; state government; per capita income; R&D